2007
DOI: 10.1265/ehpm.12.231
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Boron, Lithium, and Strontium in Human Health and Profiles of These Elements in Urine of Japanese

Abstract: The biological, medical and environmental roles of trace elements have attracted considerable attention over the years. In spite of their relevance in nutritional, occupational and toxicological aspects, there is still a lack of consistent and reliable measurement techniques and reliable information on reference values. In this review our understandings of the urinary profilings of boron, lithium and strontium are summarized and fundamental results obtained in our laboratory are discussed.Over the past decade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Strontium is one of the trace metals in the human body, belongs to the second group of periodic table along with calcium and magnesium. Calcium and strontium are very similar in their biological effects because of their chemical similarity and both of them are mainly localized in bones. , Strontium has the potential to stimulate bone formation via enhancing the expression of osteoblast-related genes, promoting osteogenic differentiation of mesenchymal stem cells, and the up-regulation of osteogenic genes such as alkaline phosphatase and osteocalcin . Moreover, it can affect bone resorption by inhibiting the activity of osteoclasts .…”
Section: Role Of Bioactive Glass Elements In the Human Bodymentioning
confidence: 99%
“…Strontium is one of the trace metals in the human body, belongs to the second group of periodic table along with calcium and magnesium. Calcium and strontium are very similar in their biological effects because of their chemical similarity and both of them are mainly localized in bones. , Strontium has the potential to stimulate bone formation via enhancing the expression of osteoblast-related genes, promoting osteogenic differentiation of mesenchymal stem cells, and the up-regulation of osteogenic genes such as alkaline phosphatase and osteocalcin . Moreover, it can affect bone resorption by inhibiting the activity of osteoclasts .…”
Section: Role Of Bioactive Glass Elements In the Human Bodymentioning
confidence: 99%
“…Daily boron intake of people in various countries has been determined as 0.89-2.12 mg/day. (17) In a study conducted in Turkey, daily boron exposure levels were measured in people living in a certain geography; blood boron and daily boron exposure levels, blood and urine boron levels, blood and semen boron levels were found to be statistically signi cant. (18) In studies, a positive correlation was observed between boron exposure and sperm motility, and a negative correlation was observed with the rate of immotile sperm.…”
Section: Resultsmentioning
confidence: 99%